Board of Directors’ Size and Profitability of Sharia Insurance in OIC Countries - Falikhatun, Falikhatun; Putri, Alfiya (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2022)
The aim of this paper was to investigate the impact of board of directors' size on the profitability ratio of public sharia insurance. A Hausman test was employed on the selection between fixed and random effects in our panel data for a sample of 58 firm-years from 2016 to 2019. Net Profit margin used as proxies for the profitability ratio. The analysis was run on the samples of sharia insurance firms were OIC Countries from Malaysia, UAE, Saudi Arabia, Qatar, Oman, Pakistan, and Bangladesh. The findings of our analyses revealed positively related and statistically significant results between board size and the profitability ratio. Tujuan dari makalah ini adalah untuk menginvestigasi pengaruh ukuran dewan direksi terhadap rasio profitabilitas asuransi syariah publik. Uji Hausman digunakan pada pemilihan antara efek tetap dan acak dalam data panel kami untuk sampel 58 perusahaan dari tahun 2016 hingga 2019. Margin Laba Bersih (NPM) digunakan sebagai proxy untuk mengukur rasio profitabilitas. Analisis dilakukan pada sampel perusahaan asuransi syariah negara-negara anggota OKI yaitu Malaysia, UEA, Arab Saudi, Qatar, Oman, Pakistan, dan Bangladesh. Temuan analisis kami mengungkapkan bahwa secara statistic terdapat pengaruh positif signifikan antara ukuran dewan direksi dengan rasio profitabilitas.